The effectiveness of corpora on Saudi EFL academic writing performance - Assrar Alharbi; Turki Alsolami (English, 2020)
This study reports on quantitative research that investigated the effects of the Corpus-Based Approach (CBA) as a pedagogical approach to Academic Writing Instruction in the context of Saudi Arabia. A total of fifteen female preparatory year students at an intermediate language proficiency level at King Abdulaziz University participated in the study. The study aimed at investigating the effect of applying corpora on learners’ lexico-grammatical abilities following a pretest-posttest design. Classroom intervention has been conducted and data were collected from written tasks over a period of time. The findings of the study demonstrated that the improvement of lexico-grammatical abilities among students is observed.